THE ADSORPTION OF GOLD(I) HYDROSULPHIDE COMPLEXES BY IRON SULPHIDE SURFACES - Widler A.M.; Seward T.M. (My University, 2002)
The adsorption of gold by pyrite, pyrrhotite, and mackinawite from solutions containing up to 40 mg/kg (8 μm) gold as hydrosulphidogold(I) complexes has been measured over the pH range from 2 to 10 at 25°C and at 0.10 m ionic strength (NaCl, NaClO4). The pH of point of zero charge, pHpzc, has been determined potentiometrically for all three iron sulphides and shown to be 2.4, 2.7, and 2.9 for pyrite, pyrrhotite, and mackinawite, respectively. In solutions containing hydrogen sulphide, the pHpzc is reduced to values below 2. The surface charge for each sulphide is therefore negative over the pH range studied in the adsorption experiments. Adsorption was from 100% in acid solutions having pH < 5.5 (pyrite) and pH < 4 (mackinawite and pyrrhotite). At alkaline pH’s (e.g., pH = 9), the pyrite surface adsorbed 30% of the gold from solution, whereas the pyrrhotite and mackinawite surfaces did not adsorb.The main gold complex adsorbed is AuHS°, as may be deduced from the gold speciation in solution in combination with the surface charge. The adsorption of the negatively charged Au(HS)2− onto the negatively charged sulphide surfaces is not favoured. The X-ray photoelectron spectroscopic data revealed different surface reactions for pyrite and mackinawite surfaces. While no change in redox state of adsorbent and adsorbate was observed on pyrite, a chemisorption reaction has been determined on mackinawite leading to the reduction of the gold(I) solution complex to gold(0) and to the formation of surface polysulphides. The data indicate that the adsorption of gold complexes onto iron sulphide surfaces such as that of pyrite is an important process in the “deposition” of gold from aqueous solutions over a wide range of temperatures and pressures.